The role of eco-enzymes in enhancing economic growth: the mediating effect of environmental sustainability in the hotel industry in Sumatra, Indonesia - Iskandar Sam; Ratih Kusumastuti; Elly Indra Swari; Derist Touriano; Mifthahul Nurzanah (Jurnal Konseling dan Pendidikan, 2025)
The pursuit of economic growth often generates environmental pressures, particularly within the hospitality sector, which is highly dependent on environmental quality. This study investigates the role of eco-enzymes in enhancing economic growth through environmental sustainability as a mediating mechanism in the hotel industry in Sumatra, Indonesia. This study adopts a quantitative explanatory research design using survey data collected from 615 general managers and duty managers of three- to five-star hotels across Sumatra. The data were analyzed using SPSS 26 through descriptive statistics, validity and reliability testing, classical assumption tests, and multiple regression analysis to examine both direct and indirect relationships among variables. The findings reveal that eco-enzyme adoption does not have a significant direct effect on economic growth. However, eco-enzymes have a significant positive effect on environmental sustainability, which in turn positively and significantly influences economic growth. These results confirm the mediating role of environmental sustainability, indicating that the economic benefits of eco-enzymes are realized indirectly through improved environmental performance rather than immediate financial outcomes. The study provides important practical implications for hotel managers and policymakers. Eco-enzyme adoption should be viewed as a strategic sustainability investment that strengthens environmental performance, enhances operational efficiency, and supports long-term economic growth. These findings contribute to the growing literature on sustainable hospitality management by empirically demonstrating the importance of environmental sustainability as a pathway linking green innovation to economic performance.